Preliminary assessment of the effectiveness of neoadjuvant chemotherapy in breast cancer with the use of ultrasound image quality indexes. (February 2023) - Pawłowska, Anna; Żołek, Norbert; Leśniak-Plewińska, Beata; Dobruch-Sobczak, Katarzyna; Klimonda, Ziemowit; Piotrzkowska-Wróblewska, Hanna; Litniewski, Jerzy
Abstract: Objective: Neoadjuvant chemotherapy (NAC) in breast cancer requires non-invasive methods of monitoring its effects after each dose of drug therapy. The aim is to isolate responding and non-responding tumors prior to surgery in order to increase patient safety and select the optimal medical follow-up. Methods: A new method of monitoring NAC therapy has been proposed. The method is based on image quality indexes (IQI) calculated from ultrasound data obtained from breast tumors and surrounding tissue. Four different tissue regions from the preliminary set of 38 tumors and three data pre-processing techniques are considered. Postoperative histopathology results were used as a benchmark in evaluating the effectiveness of the IQI classification. Results: Out of ten parameters considered, the best results were obtained for the Gray Relational Coefficient. Responding and non-responding tumors were predicted after the first dose of NAC with an area under the receiver operating characteristics curve of 0.88 and 0.75, respectively. When considering subsequent doses of NAC, other IQI parameters also proved usefulness in evaluating NAC therapy. Conclusions: The image quality parameters derived from the ultrasound data are well suited for assessing the effects of NAC therapy, in particular on breast tumors. Highlights: A method of the analysis of ultrasound data of the lesion and surrounding tissue A method of monitoring NAC therapy based on ultrasound data of breast tumors Subjects responding to NAC can be detected already after the first stage of treatment Prediction of responding and non-responding tumors with AUC of 0.88 and 0.75 The image quality parameters are well-suited for assessing the effects of NAC therapy